Pengaruh Earning per Share, Arus Kas Operasi, dan Nilai Buku Ekuitas terhadap Harga Saham dengan Profitabilitas sebagai Variabel Moderasi pada Perusahaan Index LQ45 yang terdaftar di BEI - Juliyanti Sitompul; Nisrul Irawati; Chairul Muluk (Owner : Riset dan Jurnal Akuntansi, 2022)
The objective of the research was to find out the influence of Earning per Share (EPS), Operating Cash Flow, and Book Value per Share on Stock Price in the LQ45 Index companies listed in BEI (Indonesian Stock Exchange) and to find out whether Profitability proxied by return on assets (ROA) could be used as moderating variable in this model. The research used associative causal method. The samples were 24 LQ45 companies listed in BEI (Indonesian Stock Exchange) in the period 2016-2020, taken by using purposive sampling technique. Secondary data were analyzed by using multiple linear regression analysis and interaction (moderating) test with E-views 12 software program. The result of the research showed that, partially, Earnings per Share (EPS) and Book Value per Share had positive and significant influence on stock prices while Operating Cash Flow had negative and insignificant influence on stock prices. It was also found that Return on Assets (ROA) could strengthen the correlation of Earnings per Share (EPS) with stock prices while Return on Assets (ROA) could not moderate the correlation of Operating Cash Flows and Book Value per Share with stock prices in LQ45 Index companies listed in BEI (Indonesia Stock Exchange).